Does the relationship between entrepreneurial orientation and subjective financial firm performance have an inverted U-shape? Evidence from Southeast European SMEs - Helena Šlogar; Bojan Morić Milovanović; Stella Hrvatin (Administrative Sciences, 2023)
Many academic studies have focused on exploring various interactions between entrepreneurial orientation (EO) and firm performance, where, in general, the findings confirmed their existence to be of positive character. However, many authors indicated a need to further test the possibilities concerning the nonlinearity between EO and firm performance. Moreover, since many research studies on this topic have been conducted in developed countries, there is still a need for such studies in developing countries, especially in the region of southeast Europe. Therefore, the purpose of this paper is to investigate the existence of nonlinearity between EO and subjective financial performance among SMEs in southeastern European countries. Data was collected from decisionmakers of the 963 SMEs operating in Slovenia, Croatia, Bosnia and Herzegovina, Serbia, Montenegro, and North Macedonia. Proposed hypotheses were tested using hierarchical linear regression analysis. Research results confirmed existence of the positive direct relationship EO has on financial performance, including the positive effects on sales growth and profit-to-sales ratio. On the other hand, results have not confirmed existence of nonlinearity effects that EO has on financial performance, sales growth, nor on the profit-to-sales ratio. In other words, the observed relationship does not exhibit inversed U-shape characteristics among southeast European SMEs.
Keywords: 350; entrepreneurial orientation; financial performance; nonlinearity; SMEs; southeastearn Europe